2017
DOI: 10.1002/oby.22041
|View full text |Cite
|
Sign up to set email alerts
|

Poor Health and Experiences of Being Bullied in Adolescents: Self‐Perceived Overweight and Frustration with Appearance Matter

Abstract: Body image may be an important factor in the association between weight status and the experience of being bullied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 38 publications
5
36
0
2
Order By: Relevance
“…Indeed, in late adolescence we found a negative association between BMI and peer victimization. Although our results could be a consequence of our use of a general index of victimization rather than an examination of specific subtypes, such as verbal, physical, or relational (Kukaswadia et al., ; Wang, Iannotti, & Luk, ), our findings are consistent with our hypothesis and studies that simultaneously examined psychological factors, such as body dissatisfaction (Fox & Farrow, ; Lee et al., ; Lin et al., ). Our findings further align with prior longitudinal studies that have found BMI to predict body dissatisfaction in girls and boys (Lunde, Frisén, Hwang, Frisen, & Hwang, ; Paxton, Neumark‐Sztainer, Hannan, & Eisenberg, ), and extend the literature by showing that over time this can increase risk for peer victimization among girls.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Indeed, in late adolescence we found a negative association between BMI and peer victimization. Although our results could be a consequence of our use of a general index of victimization rather than an examination of specific subtypes, such as verbal, physical, or relational (Kukaswadia et al., ; Wang, Iannotti, & Luk, ), our findings are consistent with our hypothesis and studies that simultaneously examined psychological factors, such as body dissatisfaction (Fox & Farrow, ; Lee et al., ; Lin et al., ). Our findings further align with prior longitudinal studies that have found BMI to predict body dissatisfaction in girls and boys (Lunde, Frisén, Hwang, Frisen, & Hwang, ; Paxton, Neumark‐Sztainer, Hannan, & Eisenberg, ), and extend the literature by showing that over time this can increase risk for peer victimization among girls.…”
Section: Discussionsupporting
confidence: 89%
“…The impact of peer victimization on body dissatisfaction was mostly equivalent in girls and boys, which aligns with prior research showing that bullied children are at greater risk of body dissatisfaction and weight misperception (Lee et al., ; Lin et al., ; Lunde et al., ). In later development, there was a transactional association between peer victimization and body dissatisfaction that was only present in girls, which supported our hypothesis that effects would be stronger in girls than boys.…”
Section: Discussionsupporting
confidence: 87%
“…The reason for the exclusion criterion is because prior research shows that misperception of weight status is a strong predictor of children's psychological distress, and we did not wish for this association to confound the present study. [12][13][14]…”
Section: Participants Procedure and Ethical Concernsmentioning
confidence: 99%
“…Furthermore, the positive response of middle school students was signi cantly negatively correlated with aggressive behavior, while the negative response was signi cantly positively correlated with aggressive behavior [31] . In the same setbacks, high-esteem teens were more likely to experience proactive aggression and low-esteem teens were more likely to produce reactive aggression [32,33] . Resilience refers to the dynamic process in which an individual can still adapt well in a dangerous environment [34] , which is signi cantly positively correlated with the individual's positive personality traits [35] .…”
Section: Stress-coping Model Of Left-behind Junior High School Studentsmentioning
confidence: 98%